Nominal Income and the Inflation-Growth Divide - Chand, Sheetal (IMF Working Papers; Working Paper ;, 1997)
This paper deals with aggregate demand fluctuations and their price and output effects. Starting with a nominal income solution, a rule for determining the inflation and output growth effects is presented. Assigning alternative values to the key parameters of the suggested rule generates different closure rules, such as the classical and the Keynesian and their modern counterparts. An application to major industrial country data indicates that the suggested rule is robust. Both inflation and output growth are affected by nominal shocks, but response patterns vary among the countries.